2017
DOI: 10.3390/nu9010024
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Aged Garlic Extract on Cognitive Dysfunction and Neuroinflammation Induced by β-Amyloid in Rats

Abstract: Neuroinflammation is pathological evidence of Alzheimer’s disease (AD) that likely starts as a host defense response to the damaging effects of the β-amyloid (Aβ) deposits in the brain. The activation of microglia may promote the neurodegenerative process through the release of proinflammatory cytokines, such as interleukin-1β (IL-1β) and tumor necrosis factor-α (TNFα), which may lead to neuronal damage and eventual death. Aged garlic extract (AGE) has been reported to have multiple biological activities, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 58 publications
(60 reference statements)
2
48
0
Order By: Relevance
“…These findings are identical with the results from Indonesian report, in which black garlic improves motor coordination function and the number of Purkinje cells in the cerebellar cortex of the rat brain [45]. The protection effect of black garlic on nerve system from neuroinflammation, a pathological evidence of Alzheimer's disease, and cognitive impairment has been well documented [46]. Β amyloid (Aβ) deposition leads to inflammation of the neuron, which triggers a host defense response to neuronal damage and eventually neuronal degeneration.…”
Section: Neuroprotective Effect Of Black Garlicsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are identical with the results from Indonesian report, in which black garlic improves motor coordination function and the number of Purkinje cells in the cerebellar cortex of the rat brain [45]. The protection effect of black garlic on nerve system from neuroinflammation, a pathological evidence of Alzheimer's disease, and cognitive impairment has been well documented [46]. Β amyloid (Aβ) deposition leads to inflammation of the neuron, which triggers a host defense response to neuronal damage and eventually neuronal degeneration.…”
Section: Neuroprotective Effect Of Black Garlicsupporting
confidence: 89%
“…Β amyloid (Aβ) deposition leads to inflammation of the neuron, which triggers a host defense response to neuronal damage and eventually neuronal degeneration. Nillert and collaborators had established a neuronal degenerative model by treatment with 1 μl of aggregated Aβ in the lateral ventricles; eventually they observed that ethanol extract-aged black garlic, a variant form of black garlic produced by aging the fresh garlic in room temperature, could ameliorate short-term recognition memory and inhibit activation of microglia as well as production of IL1β, a proinflammatory cytokine [46]. Additionally, ethyl acetate fraction of aged garlic extract protects PC12 neuron-like cells and ICR mice from neurotoxicity and amnesia induced by Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) [47].…”
Section: Neuroprotective Effect Of Black Garlicmentioning
confidence: 99%
“…The increased expression of synaptic proteins may underlie the improved cognitive functions (29). This effect was also accompanied by the attenuation of the loss of cholinergic neurons and neuroinflammation via the suppression of microglial activation and the secretion of interleukin (IL)-1β (30,31). Neuroinflammation plays an important role in the pathogenesis of a number of neurodegenerative disorders (32,33).…”
Section: Neuroprotective Effects Of Agementioning
confidence: 99%
“…AGE can reduce the activation of microglia and astrocytes [by immune-detection of the respective ionized calcium-binding adapter molecule 1 (Iba1) and Glial fibrillary acidic protein (GFAP) expression levels], and can thus mitigate neuroinflammatory responses (13,39). Additionally, AGE can reduce the expression levels of neuroinflammatory mediators, including IL-1β, nuclear factor (NF)-κB, TLR4, nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase 1 (HO-1) in microglial and endothelial cells and/or Aβ-induced neuroinflammation in rats (21,30,40). AGE has also been found to alleviate oxidative stress by scavenging ROS, inhibiting LDL oxidation, enhancing antioxidant signaling [such as superoxide dismutase (SOD), glutathione peroxidase (GPX) and glutathione (GSH)] and mitigating lipid peroxidation [malondialdehyde (MDA)] (41-45).…”
Section: Neuroprotective Effects Of Agementioning
confidence: 99%
“…Thus, a daily dose of 600–900 mg garlic powder proved to be effective to significantly decrease triglyceride and serum cholesterol levels . Another study showed that garlic extract exerted neuroprotective effects on cognitive dysfunction and neuroinflammation through decreasing the activation of microglia and IL‐1β to basal levels . Numerous biological effects of garlic, including antimicrobial, antioxidant, antidiabetic, anticarcinogenic, antimutagenic, anti‐atherosclerotic and immunomodulatory activities have been recently documented, and many of them are related with ageing‐dependent disorders .…”
Section: Major Medicinal Plants Used In Medication System As Anti‐agementioning
confidence: 99%